Intravenous thrombolysis versus dual antiplatelet therapy for patients with acute minor ischaemic stroke: a systematic review and meta-analysis - Qin, Bin; Fu, Lin; Qin, Huixun; Liang, Yuming; Qin, Cheng; Zhang, Jiede; Gao, Wen (Frontiers in Pharmacology, 2024)
The efficacy of intravenous thrombolysis (IVT) in patients with acute minor ischaemic stroke (AMIS) remains unclear. We performed a meta-analysis to compare the efficacy and safety of IVT and dual antiplatelet therapy (DAPT) in patients with AMIS.The Embase, Cochrane Library, PubMed, and Web of Science databases were searched up to 10 October, 2023. Prospective and retrospective studies comparing the clinical outcomes of IVT and DAPT were included. Odds ratios (ORs) and 95% confidence intervals (CIs) for early neurological deterioration (END), excellent and favourable functional outcomes, recurrent ischaemic stroke at 3 months, mortality at 3 months, and symptomatic intracranial haemorrhage (ICH) were pooled using a random-effects model.Of the five included studies, 6,340 patients were included. In patients with AMIS, IVT was not significantly associated with excellent and favourable functional outcomes, recurrent ischaemic stroke, or all-cause mortality at 3 months compared to early DAPT. However, a higher risk of symptomatic ICH (OR, 9.31; 95% CI, 3.39-25.57) and END (OR, 2.75; 95% CI, 1.76-4.30) were observed with IVT.This meta-analysis indicated that IVT was not superior to DAPT in patients with AMIS, especially in those with nondisabling AIS. However, these findings should be interpreted with caution and have some limitations. Further, well-designed randomised controlled trials are warranted. ≤ 24 * Median (interquartile range [IQR]) reported.